EVALUASI KEBIJAKAN JAMINAN KESEHATAN DAERAH DI KABUPATEN SEMARANG - Aisyah Ariandini; Warsito .; Turtiantoro . (Journal of Politic and Government Studies, 2015)
ABSTRACTTHE EVALUATION OF HEALTH INSURANCE POLICY IN THESEMARANG REGENCYHealth is the important factor, however the conditions of poor society hascaused the number of their health becomes low. The importance of health wasbecame the reason to central and local government to better concern about thoseissues, especially for the poor society, so the Central Government has released aPublic Health Insurance policy. Not all of the poor society included in toJAMKESMAS recipient list, so need some way to help the poor in health services.Through the Semarang District Government has released Regional Health Insurancepolicy (JAMKESDA) which set out in the Regent Regulations of Semarang No. 7,Year 2015. That rules is a policy in order to giving help of health services to the poorcommunities. Therefore, to determine the effectiveness of this policy, the researchproblem in this study is